2015
DOI: 10.1093/trstmh/trv025
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cure among HIV co-infected multidrug-resistant TB patients at Sizwe Tropical Disease Hospital Johannesburg, South Africa

Abstract: Cure was higher in males on ART prior to initiating MDR-TB treatment compared with males on ART after initiating MDR-TB treatment. The inverse was the case among females. Therefore, future research should explore the biological and behavioural mechanisms that may possibly be responsible for this observed trend. This will help improve MDR-TB treatment outcomes in HIV co-infected patients on ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…Similarly, male gender also increases the risk of death by two times among MDR-TB patients in South Africa [22]. However, the present study found no significant association between gender and survival among patients with MDR-TB.…”
Section: Discussioncontrasting
confidence: 71%
“…Similarly, male gender also increases the risk of death by two times among MDR-TB patients in South Africa [22]. However, the present study found no significant association between gender and survival among patients with MDR-TB.…”
Section: Discussioncontrasting
confidence: 71%
“…The study showed that time to MDR-TB treatment initiation was lower in the group diagnosed using the LPA-based algorithm compared to those diagnosed with the culture-based algorithm (50 and 66 days) which resulted in better treatment outcomes, both in terms of treatment success (65.2% vs 44.8%) and mortality (7.6% vs 15.9%) [32]. Prior to implementation of Xpert MTB/RIF as the first line diagnostic test, phenotypic DST and LPA were done on patients suspected of having DR-TB due to prior treatment failure, default, or contact with a person with known DR-TB [14]. As a result the groups of patients diagnosed in the previous algorithm may reflect a sicker population of patients with longer standing undiagnosed/untreated tuberculosis at higher risk of early mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Sizwe Tropical Disease Hospital (STDH), the inpatient treatment center, serves as a referral center for all DR-TB in Gauteng Province, where Johannesburg is located [14]. Prior to decentralization in 2011, all MDR-TB and XDR-TB patients in the province were treated at STDH; currently all XDR-TB patients are still treated there.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 3368 were MDR-TB and HIV co-infected. Study duration varied from one year [13] to over eight years [16], with majority (n = 4) of the studies conducted over periods of three to four years [14,[22][23][24]. Six studies were conducted in South Africa [14,16,[22][23][24][25], one in Lesotho [13], one in Botswana [17] and one in Ethiopia [15].…”
Section: Study Characteristicsmentioning
confidence: 99%